2013
DOI: 10.1111/gwmr.12013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shallow Geology on Volatile Organic Chemical Attenuation from Groundwater to Deep Soil Gas

Abstract: Vapor intrusion pathway evaluations commonly begin with a comparison of volatile organic chemical (VOC) concentrations in groundwater to generic, or Tier 1, screening levels. These screening levels are typically quite low reflecting both a desired level of conservatism in a generic risk screening process as well as limitations in understanding of physical and chemical processes that impact vapor migration in the subsurface. To study the latter issue, we have collected detailed soil gas and groundwater vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…A number of studies have documented the effect of high soil moisture on reducing VOC diffusion rates in the vadose zone and reducing VI potential (Figure C). , Diffusion rates are significantly lower through water-connected soils versus air-connected soils. , Field studies demonstrated that the presence of fine-grained silt or clay layers with high enough water content in the vadose zone to break the air-connected diffusion routes resulted in high VOC attenuation from groundwater to deep soil gas. This study found that, at these sites, generic groundwater to soil gas attenuation factor could be adjusted by 100-fold to account for the increased attenuation attributable to these fine-grained layers . However, because VOC diffusion is more strongly influenced by soil moisture than soil types, measuring the moisture content of fine-grained layers is an important part of evaluating their effectiveness as a VI barrier …”
Section: Vapor Intrusion Conceptual Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have documented the effect of high soil moisture on reducing VOC diffusion rates in the vadose zone and reducing VI potential (Figure C). , Diffusion rates are significantly lower through water-connected soils versus air-connected soils. , Field studies demonstrated that the presence of fine-grained silt or clay layers with high enough water content in the vadose zone to break the air-connected diffusion routes resulted in high VOC attenuation from groundwater to deep soil gas. This study found that, at these sites, generic groundwater to soil gas attenuation factor could be adjusted by 100-fold to account for the increased attenuation attributable to these fine-grained layers . However, because VOC diffusion is more strongly influenced by soil moisture than soil types, measuring the moisture content of fine-grained layers is an important part of evaluating their effectiveness as a VI barrier …”
Section: Vapor Intrusion Conceptual Modelsmentioning
confidence: 99%
“…This study found that, at these sites, generic groundwater to soil gas attenuation factor could be adjusted by 100-fold to account for the increased attenuation attributable to these fine-grained layers . However, because VOC diffusion is more strongly influenced by soil moisture than soil types, measuring the moisture content of fine-grained layers is an important part of evaluating their effectiveness as a VI barrier …”
Section: Vapor Intrusion Conceptual Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few decades, the migration of volatile organic compounds (VOCs) by diffusion from contaminated soil or groundwater into overlying buildings has received considerable attention (McHugh et al, 2013;Provoost et al, 2009). Human health risks of VOCs are typically dominated by the extent of exposure through inhalation of indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns guias sugerem que camadas de alta permeabilidade, de ocorrência natural (por exemplo, areia, cascalho ou rochas verticalmente fraturadas), também podem atuar como caminhos preferenciais para migração de vapores(API, 2005;ITRC, 2007;ITRC, 2014;USEPA, 2015).Características inerentes ao meio físico, podem atuar como fator limitador para a intrusão de vapores. Exemplos de barreiras físicas incluem: lentes de água limpa na porção superior do aquífero, camadas de silte ou argila saturadas, posicionadas acima da fonte de COVs, processos de biodegradação e/ou outras transformações físicoquímicas que podem ocorrer na zona de vadosa, bases de edificações que possuam algum tipo de impermeabilização, ventilação ou indução de pressão positiva(MCHUGH et al, 2013). A Figura 03 a seguir ilustra exemplos de barreiras potenciais para a intrusão de vapores.…”
unclassified